Communicating effectively and meaningfully with diverse families : an action oriented approach for early childhood educators - Gonzalez, Katia, 1973-; Frumkin, Rhoda, 1949- (Brill Sense, 2018)
Communicating Effectively and Meaningfully with Diverse Families: An Action Oriented Approach for Early Childhood Educators provides readers with opportunities to critically reflect upon the impact of culturally responsive practices and intercultural communication when communicating and collaborating with families. With a special focus on inclusive practices and ways to effectively develop partnerships with families, pedagogical strategies are provided highlighting specific case studies. The impact of critical reflection is also explored in this valuable monograph.